Compression strength parallel to the grain of spruce wood (Picea abies Karst) impregnated with polyurethane and acrylic coatings - Nikola Mihajlovski; Konstantin Bahchevandjiev; Mitko Nacevski (Faculty of Design and Technologies of Furniture and Interior-Skopje, 2015)
This research focuses on the influence of impregnation of spruce wood (Picea abies Karst) on the compression strength and module of elasticity of wood parallel to the grain. The wood is impregnated by double vacuum process with polyurethane and acrylic coatings. Weight percent gain of wood impregnated with polyurethane is 36.3% and 28.3% of wood impregnated with acrylic coating. Significantly increased compression strength and modulus of elasticity parallel to the grain.
Keywords: spruce, impregnation, polyurethane coating, acrylic coating, weight percent gain, compression strength, module of elasticity